Energy-Saving Technological Change and Household Energy Demand in the U.S. - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2008)
This paper deals with energy saving technical change in U.S. households' energy demand. The framework applied represents a model of demand for non-durables taking into account the durable stock and 'services' (heating/lighting and transport) that result from energy use. Embodied technical change is implemented by the average energy efficiency of the stock of energy using durables, which has been taken from a new data set compiled for this study. The efficiency has a double link with prices. On the one hand higher energy prices result in higher efficiency of installed equipment (price induced technical change). On the other hand increases in efficiency lower the corresponding service price and lead to the well known 'rebound effect'. The model makes these complex links explicit and comprises all energy relevant household consumption (transport, heating and electricity). Simulation exercises show the role of energy prices and investment in efficient appliances for policies aiming at energy saving in U.S. households.
Keywords: 330; household energy demand; embodied and induced technical change; rebound effect; Energiekonsum; Privater Haushalt; Technischer Fortschritt; Anreiz; Energieeinsparung; USA